ACTION RESEARCH ABOUT HUMAN SEXUALITY: A FREIRIAN APPROACH IN NURSING - Iara Sescon Nogueira; Célia Maria Gomes Labegalini; Karen Fernanda Ramos Pereira; Ieda Harumi Higarashi; Sonia Maria Villela Bueno; Vanessa Denardi Antoniassi Baldissera (Universidade Federal do Paraná, 2017)
The objective of this study was to describe the trajectory of a contextualized, participatory and dialogical educational action about sexuality. It was a qualitative study using critical action research, in accordance with the theoretical and methodological framework of Brazilian educator Paulo Freire. This investigation included 151 undergraduate nursing students in a public university in the northwest region of the state of Paraná, Brazil, and occurred in March 2014. Of this population, twenty students participated in the thematic investigation phase and nine in the culture circles. All ethical precepts were followed. Based on limit situations, the culture circles addressed the following themes: "The Concept of Sexuality", "Psychological and Social Dimensions of Sexuality", and "Comprehensive Care in Sexuality". The development of dialogical educational action, based on real-life problem situations was presented as a viable path for reflecting on the theme and building new knowledge for care practices involving human sexuality.